Personalized antiplatelet therapy with P2Y12 receptor inhibitors: benefits and pitfalls - Winter, Max-Paul; Koziński, Marek; Kubica, Jacek; Aradi, Daniel; Siller-Matula, Jolanta M. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Antiplatelet therapy with P2Y 12 receptor inhibitors has become the cornerstone of medical treatment in patients with acute coronary syndrome, after percutaneous coronary intervention and in secondary prevention of atherothrombotic events. Clopidogrel used to be the most broadly prescribed P2Y 12 receptor inhibitor with undisputable benefits especially in combination with aspirin, but a considerable number of clopidogrel-treated patients experience adverse thrombotic events in whom insufficient P2Y 12 -inhibition and a consequential high on-treatment platelet reactivity is a common finding. This clinically relevant limitation of clopidogrel has driven the increased use of new antiplatelet agents. Prasugrel (a third generation thienopyridine) and ticagrelor (a cyclopentyl-triazolo-pyrimidine) feature more potent and predictable P2Y 12 -inhibition compared to clopidogrel, which translates into improved ischemic outcomes. However, excessive platelet inhibition and consequential low on-treatment platelet reactivity comes at the price of increased risk of major bleeding. The majority of randomized clinical trials failed to demonstrate improved clinical outcomes with platelet function testing and tailored antiplatelet therapy, but results of all recent trials of potent antiplatelets and prolonged antiplatelet durations point towards a need for individualized antiplatelet approach in order to decrease thrombotic events without increasing bleeding. This review focuses on potential strategies for personalizing antiplatelet treatment.